IA em finanças: uma revisão sistemática - Maia, Alice Mary Ramos (Brasil, 2024)
This study conducted a literature review on artificial intelligence (AI) applied to the financial sector. Using a bibliometric approach, 532 articles published between 1986 and 2024 were collected from the Scopus database. For data analysis and visualization, the VOSviewer and Excel software were employed, identifying the leading authors, institutions, countries, and research themes. A growing body of scientific production on AI in finance has been observed since 2018, with prominent applications such as bankruptcy prediction, portfolio management, fraud detection, behavioral finance, and big data analysis. China, the United States, and India stand out as the main contributors to the literature. The findings of this study provide valuable insights for financial and technology companies, highlighting the potential of AI in strategic decision-making within the financial sector.